Synergy of Digital Transformation and Collaborative Governance: A Systematic Review of Local Government Performance - Novly Wowiling; Magdalena Wullur; Jessy J. Pondaag; Indrie D. Palandeng; Arrazin Bn Hasan Jan; Fitty Valdi Arie (Eastasouth Institute, 2026)
Post-pandemic, local governments face dual pressures to enhance public service performance through technology adoption and collaborative mechanisms. However, implementation is often hampered by system fragmentation (silos) and non-technical barriers. This study aims to synthesize recent empirical evidence regarding the interaction between digital transformation and collaborative governance, and its impact on public organization performance at the local level. This study employs a Systematic Literature Review (SLR) method following PRISMA 2020 guidelines. The search was conducted on Scopus, Google Scholar, and Garuda databases covering the 2021–2025 period. Out of 128 identified articles, 16 final articles were selected after quality appraisal using the Mixed Methods Appraisal Tool (MMAT) 2018. Findings indicate a shift in transformation forms from single-purpose applications to integrated platform ecosystems. Thematically, internal collaboration (G2G) is effective for service standardization, while external (multi-stakeholder) collaboration excels in driving innovation. The primary barriers identified are not technical, but rather human factors and organizational culture, such as sectoral egos. Conclusion: Digital technology functions merely as an enabler, not a sole solution. Significant performance improvement is achieved only when supported by cross-agency data integration (interoperability) and external pressures that force governance reform.